Your Life in web apps - Turnbull, Giles (O'Reilly, 2006)
What is a web app? It's software that you use right in your web browser. Rather than installing an application on your computer, you visit a web site and sign up as a new user of its software. Instead of storing your files on your own hard disk, the web app stores them for you, online. Is it possible to switch entirely to web apps? To run nothing but a browser for an entire day? In this PDF we'll take you through one day in the life of a web apps-only user and chronicle the pros and cons of living by browser. And if the idea of switching, fully or partially, to web apps sounds appealing to you, we also take care of the job of investigating which web apps to use. The immediate benefit of living by web apps is their accessibility: you can use almost any computer, anywhere, to retrieve your data. If you habitually switch between several computers of your own, web apps keep everything in sync and make version control simple. But there are also drawbacks to overcome: Can you trust web apps? Can you back them up? In this PDF we'll also address practicality, security issues, and backup strategies for living the web app life. Is it really possible? This PDF will help you decide.